Enhanced Creep Resistance and Mechanical Properties for CL‐20 and FOX‐7 based PBXs by Crystal Surface Modification. Issue 4 (12th February 2021) - Yang, Xuelin; Gong, Feiyan; Zhang, Kai; Yang, Wenbin; Zeng, Chengcheng; Yang, Zhijian
Abstract: Interfacial strength between energetic crystal and polymeric binder is of a great significance to the mechanical strength and other performances of polymer bonded explosives (PBXs). In this paper, hexanitrohexaazaisowurtzitane (CL‐20) and 1, 1‐diamino‐2, 2‐ dinitroethylene (FOX‐7) were chosen to study the thermal and mechanical properties of corresponding PBXs. The energetic crystals were firstly modified with polydopamine (PDA) and further coated with the hyperbranched polymer (HBP). The results showed that CL‐20@PDA achieved a noticeable retardation of 11 °C for the phase transition, due to the constraint of PDA shell, and the thermal decomposition of CL‐20 was slightly delayed. The storage modulus of CL‐20 based PBXs were improved. In addition, the tensile strength and compressive strength were increased by 22.9 % and 25.4 %, respectively. Concomitantly, the fracture failure temperature of FOX‐7 based PBXs composites after surface coating were increased, with its tensile and compressive strength increased by 33.1 % and 15.2 %, respectively. Moreover, the creep resistance of the two PBXs composites with surface modification was obviously enhanced. Abstract :